PRINCIPLES OF DOSE ADJUSTMENT IN PATIENTS WITH CHRONIC KIDNEY FAILURE - Mende, Juniarto; Kartikawati, Nurfina Dian; Titami, Arina; Mahmuda, Hartati (Jurnal Farmasi Sains dan Praktis, 2025)
Chronic renal disease is a kidney illness marked by a progressive decline in kidney function over months or years. The usage of medications in this condition is a crucial aspect of managing kidney disease patients. When done correctly, pharmacotherapy can halt disease development and minimize morbidity and mortality. In patients with kidney illness, decreasing kidney function can drastically change the pharmacokinetics and pharmacodynamics of many medications, increase the risk of drug toxicity if not well treat. Many of these changes must be expected and mitigated by changing the medicine dosage. Complications of chronic kidney disease (CKD) that go untreated can cause significant early morbidity and mortality, as well as aggravate its progression. This literature review is based on a review of the literature and articles related to CKD to determine the principles of dose adjustment in CKD patients. Classification of drugs in CKD patients includes antifungals, anticoagulants, antidiabetics, antihypertensives, antibiotics, and analgesics. The administration of these drugs should be considered for kidney function in CKD patients. The presence of multidisciplinary interventions reduces the risk of progression of CKD severity. Adjustment of the dosage regimen in CKD patients is carried out for certain drugs that have a significant relationship between drug concentration and clinical outcomes in patients.